The mechanosensory world in aquatic snakes: corporal scale sensilla in three species of Neotropical freshwater dipsadine - Velasquez-Cañon, Valeria; Bravo-Vega, Carlos; Galeano, Sandra P.; Molina, Jorge; Salazar-Guzmán, Alejandra María; García-Cobos, Daniela (Frontiers in Amphibian and Reptile Science, 2024)
Snakes have diverse and unique sensory systems that make them extremely efficient at moving through the environment while detecting prey and predators and performing courtship behaviors. In recent years, the number of studies on the mechanoreception of aquatic snakes has increased, principally focusing on the ecological and sexual roles of cephalic mechanoreceptors or sensilla. However, few studies have focused on the presence and role of corporal mechanoreceptors sensilla in freshwater snakes. This study describes the morphology of dome-shaped corporal scale sensilla for the first time in three species of aquatic Neotropical snakes (Helicops angulatus, Helicops danieli, and Helicops pastazae), using histological sections and Scanning Electron Microscopy (SEM). Histological sections revealed that the corporal sensilla resemble the previously described cephalic sensilla with a thinner beta keratin layer above the sensillum, and a group of central cells. Further, SEM images show dome-shaped protuberant organs with concentric rings. To infer possible ecological and sexual roles in corporal sensilla, we employed mixed ANOVA permutation tests to assess for differences in the number and area of sensilla between the dorsal and lateral position of the scales, and the anterior and posterior corporal region, as well as among species and sexes. Our results show that individuals across all species consistently exhibited a higher number of mechanoreceptors sensilla in the anterior and lateral region when compared to the posterior or midbody dorsal region. We qualitatively identified that scale sensilla are usually restricted to the keeled portion of the scale in the dorsal region, but are spread out throughout the scale in the lateral region. We also found differences in the average sensillum area between species, with H. angulatus exhibiting larger sensilla than H. danieli. Our results showed no evidence of sexual dimorphism in the number or area of corporal sensilla. These findings are the first to report corporal dome shaped mechanoreceptors in freshwater snakes and contribute to the understanding of mechanosensory systems in these organisms by elucidating the morphology, quantity, distribution and possible function of these corporal scale sensilla.